Case Report: Tocilizumab for Acute Kidney Graft Dysfunction in Patient Affected by COVID-19 - Barbara, Infante; Silvia, Mercuri; Dario, Troise; Giuseppe, Castellano; Stallone, Giovanni (Frontiers in Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was isolated in January 2020 and, on March, the WHO declared the status of a pandemic. It causes a cytokine release syndrome, called “cytokine storm,” characterized by systemic inflammation involving elevated levels of cytokines and hyperactivation of immune cell; this profound alteration in the immune system led to an overshooting inflammatory response contributing to morbidity and mortality. Solid organ transplant recipients are at particularly higher risk of developing critical coronavirus disease 2019 (COVID-19) due to chronic immunosuppression; in fact, establishing the balance between infection and rejection in any transplant recipient is the principal aim when prescribing immunosuppression. Tocilizumab, a humanized monoclonal antibody against interleukin-6 (IL-6) receptor widely adopted in adult rheumatoid arthritis, is used as rescue therapy for chronic antibody-mediated rejection in kidney transplantation. Data about the use of tocilizumab for treating acute kidney graft dysfunction in a setting of kidney-transplanted patients affected by COVID-19 are lacking. In this case study, we discuss the case of kidney transplant recipient with proven SARS-CoV-2 infection that develops acute graft dysfunction and the management of immunosuppression with concomitant tocilizumab administration.